Differences in Knowledge, Attitudes and Actions of Clean and Healthy Living Behaviors in School-Age Children Through Health Lore Games - Nisa, Lailatul; Gafar, Abd; Syahrum; Malibay, Salsabila (proceedinginternational, 2024)
The emergence of various diseases that often attack school-aged children is generally related to PHBS. Therefore, Instilling PHBS values in schools is an absolute necessity and can be done through a school health business (UKS) approach. The data obtained is that not all students have implemented the eight PHBS indicators at school. The aim of this research was to determine differences in respondents' knowledge, attitudes, and actions before and after being given intervention with health lore games to State Elementary School Students 09 Pandan Airmati Market Solok City, West Sumatra. The design of this research is e-quasi-experimental without any comparison group with a population of all students in grades III, IV and V. The sampling technique is by random sampling, with the number of respondents 30 people. Data was collected using a questionnaire containing knowledge and attitudes. Meanwhile, for action, use an observation sheet. Data processing and analysis are carried out individually univariate and bivariate using the t-dependent statistical test and the Wilcoxon test. The research results showed that there was a significant difference in the average level of knowledge, attitudes, and actions of students before and after being given intervention through the Health Lore game arena.